2009
DOI: 10.1074/jbc.m109.001396
|View full text |Cite
|
Sign up to set email alerts
|

Ala Scanning of the Inhibitory Region of Cardiac Troponin I

Abstract: In skeletal and cardiac muscles, troponin (Tn), which resides on the thin filament, senses a change in intracellular Ca 2؉ concentration. Tn is composed of TnC, TnI, and TnT. Ca 2؉ binding to the regulatory domain of TnC removes the inhibitory effect by TnI on the contraction. The inhibitory region of cardiac TnI spans from residue 138 to 149. Upon Ca 2؉ activation, the inhibitory region is believed to be released from actin, thus triggering actin-activation of myosin ATPase. In this study, we created a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Every 2 min (up to 12 min), a 10-l aliquot was removed into 90 l of 0.2 M perchloric acid to terminate the reaction. ATPase activity was determined from the time course (typically 6 time points/one time course) of phosphate liberation using the malachite green method (14,29). In the NEM-S1 ATPase activity measurements, the initial concentrations of S1, actin, tropomyosin, troponin were 0.2, 5.0, 1.0, 1.0 M with concentrations increased by an amount equal to the NEM-S1 to maintain the same level of free actin/tropomyosin/ troponin (6,14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Every 2 min (up to 12 min), a 10-l aliquot was removed into 90 l of 0.2 M perchloric acid to terminate the reaction. ATPase activity was determined from the time course (typically 6 time points/one time course) of phosphate liberation using the malachite green method (14,29). In the NEM-S1 ATPase activity measurements, the initial concentrations of S1, actin, tropomyosin, troponin were 0.2, 5.0, 1.0, 1.0 M with concentrations increased by an amount equal to the NEM-S1 to maintain the same level of free actin/tropomyosin/ troponin (6,14).…”
Section: Methodsmentioning
confidence: 99%
“…Thr-144 is unique to cardiac TnI (slow and fast skeletal TnI have Pro at the corresponding position). It has been demonstrated that Thr-144 is involved in length-dependent activation of cardiac muscle fibers (13) and strong cross-bridgedependent activation of actomyosin S1-ATPase activity (14).…”
Section: From the Department Of Physiology And Biophysics And Center mentioning
confidence: 99%
See 1 more Smart Citation
“…Thr143 is a cardiac-specific residue (proline in skeletal muscle) located in the inhibitory region of cTnI (residues 137-148 of the human cTnI sequence). In the absence of Ca 2+ , this region interacts with actin and thereby inhibits actomyosin ATPase activity, while upon Ca 2+ binding to cTnC, the inhibitory region interacts with the N-terminal regulatory domain of cTnC, allowing actin to interact with myosin Kobayashi et al 2009;McKay et al 1999). Alanine substitution of Thr143 did not have any significant effect on the Ca 2+ -sensitivity of force, but there was the involvement of strong cross-bridge-dependent activation of the thin filaments in the absence of Ca 2+ (Table 1) (Kobayashi et al 2009).…”
Section: Thin Filament Regulationmentioning
confidence: 99%
“…In the absence of Ca 2+ , this region interacts with actin and thereby inhibits actomyosin ATPase activity, while upon Ca 2+ binding to cTnC, the inhibitory region interacts with the N-terminal regulatory domain of cTnC, allowing actin to interact with myosin Kobayashi et al 2009;McKay et al 1999). Alanine substitution of Thr143 did not have any significant effect on the Ca 2+ -sensitivity of force, but there was the involvement of strong cross-bridge-dependent activation of the thin filaments in the absence of Ca 2+ (Table 1) (Kobayashi et al 2009). Also, a reduction in myofilament length-dependent activation has been observed in cardiac rat trabeculae expressing slow skeletal troponin (ssTn), which has a proline at position 122 versus a threonine at position 143 in cTnI (Table 1) (Tachampa et al 2007).…”
Section: Thin Filament Regulationmentioning
confidence: 99%